Feeding common carp fish on diets containing different percentages of ginger (Zingbar officinale) and its effect on the characteristics of the blood and biochemical parameters - al-Kurjia, Umar Abd al-Hamid (مجلة العلوم الزراعية و البيئية و البيطرية : مجلة علمية محكمة ربع سنوية., 2023)
Common carp (Cyprinus carpio L.) were manually fed a diet supplemented with ginger powder (Zingiber officinalis) at levels (0, 6, 8, and 10) % to observe the effect of ginger powder on blood and biochemical parameters. The research was conducted in the fish laboratory of the Faculty of Animal Production /College of Agriculture and Forestry/University of Mosul. In this study 84 fish were used and distributed over 12 glass tanks with an average weight of 28 ± 1gm. The fish were fed 3 times a day at a rate of 3% of body weight for a period of 56 days. At the end of the experiment, there were significant differences (P <0.05) in the hemoglobin standard in the treatments to which ginger was added compared to the control treatment. PCV values also increased in fish fed on the added diets. Also, albumin values decreased in treatments to which ginger was added compared to the control treatment, and globulin values decreased in treatment 2 (6% ginger). There were also no significant differences in the total protein standard between the control treatment and the treatments to which ginger was added, except for the treatment which had an 8% level of ginger. The level of glucose also decreased significantly in blood of fish fed on ginger compared to the control treatment. while the values of cholesterol and triglycerides varied for the ginger treatments compared to the control treatment. Also the values of Aspartate Transaminase enzyme (AST) decreased in the treatments to which ginger was added compared to the fish fed on the control diet and Alanine Transaminase enzyme (ALT) values also decreased in all treatments that had ginger added to it compared to the control except for the fourth treatment (10% ginger), which was higher than the rest of the treatments. Feeding fish diets containing ginger lowered hemoglobin in the blood. تم تغذية أسماك الكارب الشائع (Cyprinus carpio L.) على علائق تحتوي على نسب مختلفة من مسحوق الزنجبيل (0، 6، 8، 10) % بهدف دراسة تأثير مسحوق الزنجبيل على الدم والمعايير الكيموحيوية. أجريت الدراسة في مختبرات الأسماك التابعة لقسم الإنتاج الحيواني في كلية الزراعة والغابات / جامعة الموصل-العراق. أستخدم في هذا البحث 84 من أسماك الكارب الشائع بمعدل وزن 28 ± 1 غم، وزعت الأسماك على 12 حوضا زجاجيا وتم تغذيتها 3 مرات يوميا وبمعدل 3% من وزن الجسم الحي لمدة 56 يوما. في نهاية التجربة تم تسجيل فروقات معنوية (P<0.05) في مستوى الهيموكلوبين فيما يخص المعاملات التي احتوت على الزنجبيل بالمقارنة مع معاملة السيطرة، أيضا كان هنالك ازدياد في مستويات PCV في الأسماك التي تغذت على العلائق المحتوية على الزنجبيل ، بينما لوحظ انخفاض في مستويات الألبومين في المعاملات التي احتوت على الزنجبيل مقارنة بمعاملة السيطرة، تم تسجيل انخفاض في مستوى الكلوبيولين في المعاملة الثانية التي احتوت على( 6 % من الزنجبيل)، وتم تسجيل فروقات معنوية في البروتين الكلي في المعاملة التي احتوت على (8 % من الزنجبيل) مقارنة بمعاملة السيطرة، مستوى الكلوكوز انخفض معنويا في دم الأسماك التي تغذت على الزنجبيل مقارنة بمعاملة السيطرة، بينما اختلفت قيم الكوليسترول والكليسيريدات الثلاثية في المعاملات التي المحتوية على الزنجبيل مقارنة بمعاملة السيطرة، أيضا لوحظ انخفاض في مستويات أنزيم AST في الأسماك التي احتوت علائقها على الزنجبيل مقارنة بمعاملة السيطرة، وانخفض مستوى أنزيم ALT في جميع المعاملات ما عدا المعاملة الرابعة (10 % زنجبيل) التي كانت أعلى من باقي المعاملات. إن تغذية الأسماك على علائق تحتوي على الزنجبيل أدت الى انخفاض في مستوى الهيموغلوبين في الدم.